A Wideband Eight-Element MIMO Antenna Array in 5G NR n77/78/79 and WLAN-5GHz Bands for 5G Smartphone Applications - Jun-Yi Jiang; Hsin-Lung Su (International Journal of Antennas and Propagation)
In this paper, a wideband eight-element multiple-input multiple-output (MIMO) antenna array for 5G smartphone applications is presented. Each antenna is composed of a dual-arm tortuous monopole radiating element with a double-stub tuner and an open slot on the ground plane. Tuning stub microstrip lines are utilized to improve impedance matching. The operating bandwidth of the single antenna element is from 3200 to 6000 MHz with three resonant frequencies. The operating bandwidth covers the 5G new radio (NR) bands (n77/n78/n79) and the WLAN-5GHz band. The isolation of the proposed MIMO antenna array is above 10 dB in the entire operating band without any isolation elements. Furthermore, the proposed MIMO array was manufactured and measured. The measured results validate that the MIMO antenna array has a wide 6-dB impedance bandwidth from 3.2 to 6 GHz and the isolations are all more than 10 dB. The total efficiency ranges from 38% to 83%. The above results show that this MIMO antenna array can support 5G applications in smartphones.